THE EFFECT OF MANAGERIAL OWNERSHIP, LEVERAGE AND PROFITABILITY ON DIVIDEND POLICY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA - nurlaila (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims to determine the effect of managerial ownership, leverage and profitability on dividend policy on manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sampling technique in this study used purposive sampling and obtained 66 samples of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The results of this study indicate that managerial ownership, leverage and profitability simultaneously have positive and significant effects on dividend policy. While partially only profitability variables that have a positive and significant effect on dividend policy and for managerial ownership and leverage variables do not have a significant effect on dividend policy.